Strategy 2023-2030: Conserving, restoring and sustainably managing forest and tree genetic resources in Asia and the Pacific - Asia Pacific Forest Genetic Resources Programme (APFORGEN) (2023)
Asia-Pacific Forest Genetic Resources Programme (APFORGEN) is a regional programme and network for the conservation of forest and tree genetic resources. Through its network of geneticists, forestry professionals and funding partners in 15 Asian countries, APFORGEN shares knowledge and good practices, implements multi-country research and development projects, operates a Regional Training Centre and serves as a one-stop-centre on forest and tree genetic resources information and initiatives in the Asia-Pacific. This document describes APFORGEN's regional strategy for 2023-2030, outlining four strategic objectives and respective targets for each: 1. Mobilize political and financial support for integrated management of forest genetic resources in land use, biodiversity and climate policies, strategies and programmes 2. Make information about the region’s forest and tree genetic resources available and accessible to support their sustainable management and research 3. Develop conservation and sustainable use strategies for regionally important and threatened tree species 4. Strengthen tree seed systems to facilitate ecosystem restoration, support local livelihoods and climate change adaptation and mitigation